2013
DOI: 10.3892/mmr.2013.1871
|View full text |Cite
|
Sign up to set email alerts
|

Dendroaspis natriuretic peptide is degraded by a metalloproteinase in the rat kidney

Abstract: Abstract. Our previous study demonstrated that the concentration of dendroaspis natriuretic peptide (DNP) was markedly higher than that of atrial NP (ANP) in rabbit plasma, indicating that DNP has a different metabolic rate from other NPs. Therefore, the metabolic characteristics of DNP in mammals require further analysis. The stabilities of NPs were determined by incubating 125 I-labeled ANP, brain NP (BNP), C-type NP (CNP) and DNP at 37˚C for 1, 2 and 4 h, and analyzing their profiles by reversed-phase high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The natriuretic peptide receptors (NPRs) for DNP have been reported to localize to the smooth muscle tissue of the human mammary artery (4); in addition, DNP has been observed to induce vasodilatation via the direct activation of these receptors (7). Our previous studies provided evidence that DNP exerts renal actions via the NPR-A subtype and demonstrated that DNP and its specific receptor are present in the kidneys of rabbits (8)(9)(10). Collectively, these results suggested that DNP has a physiological role in regulating the renal function of mammals by interacting with specific NPRs, which have a particular guanylyl cyclase (pGC) domain.…”
Section: Introductionmentioning
confidence: 99%
“…The natriuretic peptide receptors (NPRs) for DNP have been reported to localize to the smooth muscle tissue of the human mammary artery (4); in addition, DNP has been observed to induce vasodilatation via the direct activation of these receptors (7). Our previous studies provided evidence that DNP exerts renal actions via the NPR-A subtype and demonstrated that DNP and its specific receptor are present in the kidneys of rabbits (8)(9)(10). Collectively, these results suggested that DNP has a physiological role in regulating the renal function of mammals by interacting with specific NPRs, which have a particular guanylyl cyclase (pGC) domain.…”
Section: Introductionmentioning
confidence: 99%